High Surface Area Ortho-Nb2O5 as Bifunctional Adsorbent and Photocatalyst for Efficient Removal of Tetracycline Antibiotics from Wastewater - Taher, Tarmizi; Maharani, Putri; Muhtar, Sephia Amanda; Munandar, Andika; Sidiq, Ahmad Nur; Rianjanu, Aditya (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The presence of antibiotics in aquatic environments poses significant environmental and health risks, requiring advanced treatment strategies for their removal. In this study, we report the straightforward hydrothermal synthesis of high surface area ortho-Nb2O5 and its dual role as both an adsorbent and photocatalyst for the removal of tetracycline (TC) from wastewater. The structural and morphological properties of ortho-Nb2O5 were systematically investigated using XRD, FTIR, FESEM-EDS, and BET surface area analysis. The ortho-Nb2O5 synthesized at 72 hours (Nb2O5_72) exhibited a high BET surface area of 242.42 m2/g, mesoporosity, and a bandgap of 3.28 eV, enabling efficient UV-driven photocatalysis. Adsorption studies revealed a high TC removal capacity of 32 mg/g at equilibrium. Under UV irradiation, ortho-Nb2O5 achieved significant photocatalytic degradation of TC.